2012
DOI: 10.1007/s13149-012-0210-8
|View full text |Cite
|
Sign up to set email alerts
|

Description des intoxications notifiées dans la région de Marrakech-Tensift-Al Haouz au Maroc entre 1981 et 2008

Abstract: In Morocco, the Marrakech-Tensift-Al Haouz region is one of the 16 regions most affected by poisoning. The aim of this study was to determine the epidemiological profile of poisoning recorded in the study region. A retrospective study of poisoning cases, declared between 1981 and 2008 in the Morocco Poison Control and Pharmacovigilance Center, was conducted. During the study period, 8517 poisoning cases were collected. The average age of patients was 22 ± 15 years. The male/female sex ratio was 0.85. Food pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Similar to findings from other studies [9, 12], our data analysis found that adults and adolescents were most represented in drug poisoning (median age 21 years). We found a predominance of females in the total number of drug overdoses, similar to findings in other countries [6, 1215].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to findings from other studies [9, 12], our data analysis found that adults and adolescents were most represented in drug poisoning (median age 21 years). We found a predominance of females in the total number of drug overdoses, similar to findings in other countries [6, 1215].…”
Section: Discussionsupporting
confidence: 90%
“…Over the period 2004–2016, the number of drug poisoning cases reported in the provincial delegation of health in Errachidia increased year on year, which is similar to results described in other regions of the country [8–11]. Drug poisoning is the primary cause of poisoning in the oriental (north Morocco) and Marrakech–Tensift–Al Haouz (central Morocco) regions [9, 11]. The increasing menace of drug poisoning is alarming.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The mean age was 28.6 ± 17.8 years. As a consequence, young adults were the most affected, which is consistent with the findings in other Moroccan regions ( [9][10][11]16,19]). This age group should be given special attention, with frequent monitoring of university residences and increased knowledge of appropriate food hygiene practices.…”
Section: The Reported Cases In This Study Were From An Urban Area Like As Other Moroccan Regions ([101617]supporting
confidence: 90%